The small and medium-sized enterprise sector in Poland. (7th July 2008) - Kunasz, Marek
The paper presents the analysis of the state and importance of the small and medium-sized enterprise sector in Poland. Theoretical part deals with the role SME sector plays economic growth and development, and kinds of barriers and instruments used to support the development of entrepreneurship institutionally. With respect to empirical part, statistical comparative analysis of measures commonly accepted in the literature that reflect the state and importance of the small and medium-sized enterprise sector in the years 1994?2006 was made (the span of time devoted to the research).